FACTORS AFFECTING COST OF EQUITY - Widjaja, Rivaldi; Yanti, Yanti (International Journal of Application on Economics and Business, 2024)
This research aims to examine the effect of board commissioners' effectiveness, family ownership, and audit quality on the cost of equity in the Infrastructure sector in Indonesia. The Infrastructure sector in Indonesia lags behind other countries, necessitating greater attention. The sample for this research, based on the purposive sampling strategy, consists of 34 infrastructure firms (168 observations) listed on Indonesian Stock Exchanges for the period 2018 to 2022. These factors include the effectiveness of the board of commissioners (as measured by the good, fair, and poor ratings [DEKOM]), family ownership (as measured by family control rights [FAMOWN]), and audit quality (as measured by the big four KAP and non-big four [QUAD]). SPSS 23 was used to test the data processing in this research. This research analysis uses a multiple regression analysis approach. The first hypotheses is that the effectiveness of the board of commissioners has a negative effect on equity costs. The second hypotheses is that family ownership has a positive effect on equity costs. Lastly, the third hypotheses is that audit quality has a negative effect on equity costs. The findings of this research indicate that the effectiveness of the board of commissioners and family ownership have no effect on the cost of equity. However, audit quality has a positive and significant impact on the cost of equity. Hence, it can be concluded that the first, second, and third hypotheses in this study are rejected.